Geographic Location Determines Differentially Methylated Gene Expressions in Autoimmune Diseases - Jacques-Olivier Pers; Hajar Bahane; Christelle Le Dantec; Nathan Foulquier; Marta E. Alarcon-Riquelme; Pierre Youinou; PRECISESADS Clinical Consortium (Immuno, 2021)
Further observations support the role of environmental factors in autoimmune diseases via the alteration of the epigenetic machinery. In this context, ultraviolet light, smoking, chemicals, and psychological stress have been described as likely examples of this phenomenon. For this study, we took advantage of the PRECISESADS IMI project, which gathered joint data from 2500 individuals with systemic autoimmune diseases, including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), primary Sjögren’s syndrome (pSS), rheumatoid arthritis (RA), primary antiphospholipid syndrome (PAPS), and mixed connective tissue disease (MCTD), and aimed to determine such epigenetic modifications in SLE, SSc, pSS, and RA patients. Here, we performed a set of measures in several countries from the north and south of Europe. We observed that autoimmune patients from the north of Europe presented a higher hypomethylated profile associated with an increased gene expression than patients from the south. These genes were associated with interferon (IFN) pathways, immunity, and the pathways associated with cellular metabolism. Since the IFN scores were increased in this population, these patients presented a more inflammatory profile. To conclude, the geographical location of patients with autoimmune diseases has an impact on DNA methylation, RNA expression, and immunological profiles.